INCREASING CUSTOMER SATISFACTION THROUGH PRODUCT QUALITY AND UNIQUE PACKAGING - Erwan, Dona; Tuti, Meylani (ESENSI: Jurnal Manajemen Bisnis, 2024)
This research aims to help researchers understand whether there is an impact of product quality and packaging on purchasing decisions and customer satisfaction levels. The population in this research is Fore consumers. The sample method used was purposive sampling with a total of 252 respondents. The sample in this research is consumers who have purchased or consumed Fore products at least twice. The data analysis method uses a structural equation model with the help of smartPLS software. The results of this research show that there is a positive and significant influence of packaging on purchasing decisions, product quality on purchasing decisions, packaging on customer satisfaction, and product quality on customer satisfaction. Overall, these findings underscore the importance of effective packaging strategies and improving product quality in achieving sustainable customer satisfaction in the coffee shop industry. Each packaging variable and product quality have an important role in shaping consumer perceptions, driving purchasing decisions, and influencing the level of customer satisfaction.